Ecofeminist Perspectives on Nubian Women's Roles: Bridging Tradition, Ecology, and Language Preservation - Imam Wicaksono; Sherif Sa’ad alGayyar; Ahmed Hassan Mohammad Hassan (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
This study integrates viewpoints from Vandana Shiva and Maria Mies to investigate Nubian women's responsibilities as agents of cultural, ecological, and linguistic sustainability within an ecofeminist framework. Three interconnected aspects are the subject of the study: their contributions to language preservation, ecological management, and cultural traditions. This study synthesizes knowledge from academic sources on Nubian women's adaptive tactics in the face of socio-ecological disturbances, including the relocation caused by the Aswan High Dam, through a qualitative literature review and thematic analysis. According to the research, Nubian women preserve intangible cultural heritage by striking a balance between modernity and customs like storytelling, rituals, and crafting. Their ecological roles, which include resource management, the use of natural materials, and sustainable agriculture techniques, show how important they are to preserving environmental equilibrium. Linguistically, Nubian women preserve their language through folklore, songs, and everyday communication, ensuring intergenerational transmission of cultural identity. This research underscores the interconnectedness of gender, culture, and ecology, providing a model for cultural resilience and sustainability in marginalized communities globally. The implications extend to broader discussions on sustainable development, gender studies, and strategies for integrating localized resilience into global challenges.